KORELASI KEPATUHAN TERAPI BERBASIS INSULIN DENGAN EFEKTIVITAS TERAPI PADA PASIEN DIABETES MELITUS TIPE 2 DI RSUD ULIN BANJARMASIN - Dedi Hartanto; Risya Mulyani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
Diabetes mellitus increases the risk of complications that can cause significant quality of life problems. Complications can be prevented by controlling the effectiveness of therapy (HbA1c value). The use of early insulin is beneficial to reduce mortality, morbidity and glucose toxicity. However, there are obstacles in using insulin such as pain during insulin injections, weight gain, and high cost. Therefore, the possibility of patients not adhering to therapy is also great. This study aims to determine the picture of adherence and effectiveness of therapy (HbA1c value) in DM patients with insulin therapy. This research is a nonexperimental research with cross-sectional research design. The data were collected prospectively in patients with type 2 DM in Pharmacy Installation of Ulin Banjarmasin Hospital. The univariate analysis aimed to see the result of data description of individual characteristics, adherence level, and HbA1c value while bivariate analysis used was chi-square test to see the relation between adherence therapy to therapy effectivity (HbA1c value). The results showed that respondents who adhered to therapy only 25% while others 75% considered non-adherent to therapy. In addition, respondents who have good effectiveness or controlled HbA1c value (6.5%) only 3.6% while others 96.4% effectiveness of therapy has not been well controlled. There was a positive and significant correlation between treatment adherence level and HbA1c value (r = 0,799; p0,05). It can be concluded that adherence to insulin-based therapy should still be improved and improved adherence therapy may improve HbA1c control values.